Supervisi Pendidikan Islam: Telaah Model Pengawasan Madrasah di Kota Sorong - Chudzaifah, Ibnu (Tarbiyah STAIN Sorong, 2019)
The success of educational supervision in madrasas as a supervisory function which represents one of the important factors in education management has not been optimally touched in the educational development program in madrasah. Whatever is the target for supervision in conducting supervision in madrasah. This research is a field or field research (field research) with a qualitative descriptive analysis method. The focus of this research is about the role and challenges of supervision of Islamic Education in the City of Sorong by using a type of field research, with descriptive qualitative analysis methods. The results of this study are: First, the role of school supervisors in madrasah in Sorong City is in accordance with existing regulations, according to very limited in the sense of regulating the place of madrasas that are supervised, but the investment of madrasah supervisors is very beneficial and beneficial in the development and encouragement of educators and education staff in Sorong City. Second, the obstacle that was transferred by the madrasah supervisor in Sorong City was the time of supervision in the madrasa, the limited number of madrasah supervisors, limited operational funds and financial support from the Ministry of Religion.